'Altering the structure of society': an institutional focus on Virginia Woolf and working-class education in the 1930s. Issue 8 (14th September 2018) - Periyan, Natasha
ABSTRACT: Where previous analyses of Virginia Woolf's relationship to working-class education by Melba Cuddy-Keane and Beth Rigel Daugherty have focused on the role of the public library and Woolf's Common Reader essays, this article explores Woolf's interest in institutional applications of working-class education in The Years (1937) and 'The Leaning Tower' (1940). It argues that Woolf drew on contemporaneous educational debates in her analysis of the educational institution's role in the cultivation of cultural and political democracy. The article builds on work by Anna Snaith and Alice Wood that has considered the influence of dialect scholar Joseph Wright on Woolf's characterisation of Sam Robson in The Years . It further suggests the significance of Wright for a reading of the children's song that explores its signifying role as a marker of educational division. 'The Leaning Tower', Woolf's lecture to the Workers' Educational Association, is assessed as a studied rhetorical performance that draws on contemporaneous educational debates as Woolf anticipates a socially and culturally democratic future in the post-war world that is 'struggling to be born' (Virginia Woolf, The Essays of Virginia Woolf Volume 6 1933–1941 (London: Hogarth Press, 2011), p. 276).